Optimal dual-pressure evaporation organic Rankine cycle for recovering waste heat from compressed air energy storage (CAES) - Zhong Ge; Yanlei Zhai; Jian Li; Jianbin Xie; Zhiyong Xie; Fubin Yang (Case Studies in Thermal Engineering, 2024)
Compressed Air Energy Storage (CAES) is an effective solution to the problems of the intermittency and volatility of renewable energy. However, the process of compressing air consumes energy and converts it into low-temperature waste heat, limiting the improvement of round-trip efficiency. This paper introduces the dual-pressure evaporation organic Rankine cycle (ORC) to recover the waste heat from the CAES system compression process, which enhances the round-trip efficiency. Optimal working fluids and design schemes of parallel and series dual-pressure evaporation ORCs are analyzed. The thermodynamic performance of two cycle types is compared. The exergy loss distribution characteristics of the dual-pressure evaporation ORC are explored, and the impact on the round-trip efficiency of the CAES system is evaluated. Results show that the parallel dual-pressure evaporation ORC has better performance with an optimum working fluid of R1234yf and a maximum waste heat conversion efficiency of 9.3 %. The round-trip efficiency of the CAES system will be relatively increased by 5.2 % by introducing the parallel dual-pressure evaporation ORC. The maximum exergy efficiency of the parallel dual-pressure evaporation ORC is 52.8 %, and the condenser and low-pressure stage expander have larger exergy losses, accounting for 33.8 % and 22.0 % of the total losses, respectively.